Hak Remisi Dan Asimilasi Narapidana Di Indonesia Dalam Perspektif Hak Asasi Manusia - Manggala Gita Arief Sulistiyatna (Universitas Islam Indonesia, 2021)
This research aims to determine the regulation of remission and assimilation rights for prisoners in Indonesia, as well as the arrangement is ideal in the perspective of human rights. This is a normative juridical research that uses conceptual and statutory approaches. The results of the study show that the remission arrangement is still scattered in several rules and not in one comprehensive rule. The tightening by providing special conditions for prisoners of certain criminal acts in Article 34A of Government Regulation Number 99 of 2012 actually contains the problem of conflict between legal norms itself and there are also problems related to the loss of equal opportunity and equality before the law which is a human right that must be protected, including for prisoners. Strengthening the role of remission and assimilation is not only a right of prisoners, but also as a tool to provide motivation as well as appreciation for prisoners who have truly improved themselves. Therefore, there is a need for special rules governing remissions that cover all matters concerning remission, both the type of remission, the amount of remission, when it is given, the conditions and simple procedures and the authorized official to give it.Key Words: Assimilation; human rights; remissionAbstrakPenelitian ini dilakukan untuk mengetahui pengaturan hak remisi dan asimilasi bagi narapidana di Indonesia, serta bagaimana pengaturannya yang ideal dalam perspektif hak asasi manusia. Penelitian ini merupakan penelitian yuridis normatif yang menggunakan metode pendekatan konspetual dan pendekatan perundang-undangan. Hasil penelitian menyimpulkan pengaturan remisi masih tersebar dalam beberapa aturan dan tidak menjadi satu aturan yang komprehensif. Pengetatan dengan pemberian syarat khusus terhadap narapidana tindak pidana tertentu dalam Pasal 34A Peraturan Pemerintah Nomor 99 Tahun 2012 justru mengandung masalah pertentangan antar norma hukum itu sendiri dan juga ada permasalahan terkait hilangnya kesempatan dan persamaan yang sama di depan hukum dimana hal tersebut merupakan hak asasi manusia yang harus dilindungi termasuk bagi narapidana. Penguatan peran remisi dan asimilasi bukan hanya sebagai hak narapidana, namun juga sebagai alat untuk memberikan motivasi sekaligus penghargaan bagi narapidana yang telah sungguh-sungguh memperbaiki diri. Oleh karena itu, perlu aturan khusus yang mengatur tentang remisi yang mencakup seluruh hal tentang remisi baik jenis remisi, besaran remisi, kapan diberikannya, syarat-syaratnya serta prosedur sederhana dan pejabat yang berwenang memberikannya.Kata Kunci: Remisi; asimilasi; hak asasi manusia